Assessment of the Hemophagocytic Lymphohistiocytosis HScore in Patients With Coronavirus Disease 2019. (28th September 2020) - Clark, Kristina E N; Nevin, William D; Mahungu, Tabitha; Lachmann, Helen; Singh, Animesh
Abstract: The clinical manifestation of moderate to severe coronavirus disease 2019 (COVID-19) has parallels to secondary hemophagocytic lymphohistiocytosis (HLH) both clinically and based on molecular inflammatory response. We found no evidence to support the utility of risk-stratifying COVID-19 patients using risk scoring methodology designed for HLH.